Development of a Problem-Based Learning-Oriented Interactive E-worksheet on Chemical Equilibrium to Enhance Students' Scientific Literacy Skills - Rachma Mufidah; Kusumawati Dwiningsih (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Indonesian students' scientific literacy scores decreased by 13 points from PISA 2018, indicating that the scientific literacy skills of participants in Indonesia are low. One area of concern is students' understanding of chemical equilibrium, which is essential because it is a prerequisite for grasping subsequent materials. This study aims to assess the feasibility of interactive e-worksheets as a learning medium for chemical equilibrium material in terms of validity, practicality, and effectiveness. According to Thiagarajan, the research employs the 4-D research and development model, which includes Defining, Designing, Developing, and Disseminating but is limited to the development stage. A limited trial was conducted using a one-group pretest-posttest research design. Validation results show that the interactive e-worksheet is valid with a mode value of 4 in content, presentation, language, and design. The validity test results yielded a mode value 4 for both content and construct validity. The practicality test results indicated a high percentage of practicality with very practical criteria. The effectiveness test, analysed using n-gain, showed an n-gain value of 0.78 with high criteria, and the paired sample t-test results indicated a P-value of 0.000, confirming that the post-test scores were significantly higher than the pretest scores. Thus, the PBL-oriented Interactive e-worksheet can improve students' scientific literacy skills.